Stages of change in physical activity-related behavior in adolescents from a Brazilian state capital - Andreia Pelegrini; Diego Augusto Santos Silva; Herton Xavier Corseuil; João Marcos Ferreira de Lima Silva; Edio Luiz Petroski (Universidade Estadual Paulista (UNESP), 2013)
The purpose of this study was to investigate the stages of change in physical activity-related behavior (EMCRAF) and their association with gender and age. A total of 1108 high school students of both sexes, from Florianópolis, State of Santa Catarina, took part in this study. A questionnaire was used to assess EMCRAF. A higher proportion of boys were in the maintenance stage (48.1%) and a higher proportion of girls were in contemplation (24.7%) and pre-contemplation (6.4%) stages. Gender factor male and age range 17-18 were protective factors, which increased the likelihood of physically active behavior. Girls aged 17-18 were twice as likely to be in the contemplation stage than boys. It is important to expand knowledge about EMCRAF in adolescents and their associations with gender and age because a considerable number of behaviors established during this period of life can last into adulthood.